IMPLEMENTASI PENCEGAHAN PADA PENEBANGAN ATAU PEMBALAKAN LIAR DITINJAU DARI UNDANG-UNDANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN NO. 18 TAHUN 2013 - Muhammad Ramdhan Hananto; Tundjung Herning Sitabuana (Fakultas Hukum Universitas Tarumanagara, 2022)
The environment is the environment in which we live and the source of our life comes from the environment.The environment should be our responsibility to always care for and protect it. Meanwhile, illegal logging orillegal logging is the felling of trees in the forest without permission from the government to fulfill their owninterests. Therefore, it is necessary to make observations regarding this matter in a manner regulated in theapplicable articles. So that the community does not do things that can harm our environment and protect thenatural resources that exist in the territory of the Republic of Indonesia. Ef orts are being made by theIndonesian government to overcome this problem by making a basic law on the prevention and eradication offorest destruction. If it can prevent and eradicate forest destruction ef ectively and can provide a deterrentef ect, a strong legal basis is needed and is able to guarantee the ef ectiveness of law enforcement